Regional groundwater modeling of the guarani aquifer system - Gonçalves, Roger D. [UNESP]; Teramoto, Elias H. [UNESP]; Chang, Hung K. [UNESP] (MDPI, 2020)
The Guarani Aquifer System (GAS) is a strategic transboundary aquifer system shared by Brazil, Argentina, Paraguay and Uruguay. This article presents a groundwater flow model to assess the GAS system in terms of regional flow patterns, water balance and overall recharge. Despite the continental dimension of GAS, groundwater recharge is restricted to narrow outcrop zones. An important part is discharged into local watersheds, whereas a minor amount reaches the confined part. A three-dimensional finite element groundwater-flow model of the entire GAS system was constructed to obtain a better understanding of the prevailing flow dynamics and more reliable estimates of groundwater recharge. Our results show that recharge rates effectively contributing to the regional GAS water balance are only approximately 0.6 km3/year (about 4.9 mm/year). These rates are much smaller than previous estimates, including of deep recharge approximations commonly used for water resources management. Higher recharge rates were also not compatible with known 81Kr groundwater age estimates, as well as with calculated residence times using a particle tracking algorithm.
Keywords: Finite element method (FEM); Groundwater age; Groundwater modeling; Groundwater recharge; Guarani Aquifer System (GAS); Numerical modeling; Water resources management